1996
DOI: 10.1097/00007632-199606150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Severity of Myelopathy in Atlantoaxial Instability

Abstract: Neurologic symptoms were found to be closely related to the morphology of the spinal cord. Compression ratio and the C1-C2 ratio were found to be useful in understanding neurologic symptoms. The C1-C2 ratio seems to serve as an important predictor of the prognosis of atlantoaxial instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The average recovery rate of JOA score from before surgery to the final follow-up, calculated as proposed by Hirabayashi et al [18], was 51.4% (range -12.5 to 100%). On the radiographs, the C1-C2 angle [25] was measured before surgery and after fusion was confirmed. The results showed that the average C1-C2 angle improved from 22.3°preop-eratively (range 5°-59°) to 19.6°postoperatively (2°-59°).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average recovery rate of JOA score from before surgery to the final follow-up, calculated as proposed by Hirabayashi et al [18], was 51.4% (range -12.5 to 100%). On the radiographs, the C1-C2 angle [25] was measured before surgery and after fusion was confirmed. The results showed that the average C1-C2 angle improved from 22.3°preop-eratively (range 5°-59°) to 19.6°postoperatively (2°-59°).…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative reduction with skeletal traction may be of great assistance in achieving a successful outcome of the surgery. In recent years, a number of new techniques for internal fixation of the atlantoaxial complex and odontoid fracture have been described [15,20,25,37]. However, atlantoaxial arthrodesis is only indicated in a reduced position.…”
Section: Discussionmentioning
confidence: 99%
“…This is an area of particular interest due to the fact that in humans, this region is frequently affected by different alterations of medical importance, such as illness of the motor neurones (Murakami, 1990) and the atlantoaxial uncertainty (Nakajima et al, 1996). In Veterinary Medicine, pathological alterations like cervical spinal stenosis (Bhatti et al, 2001;Doige, 1988;Trotter, 1972); neoplasias (de Lahunta, 1983;Jubb and Huxtable, 1993;Thomas et al, 1997); copper deficiency in small ruminant (Storts, 1988); poliomielomalacia of the pig intoxicated with selenium (Baker et al, 1989;Penrith, 1995); muscular atrophy of German shepherd's spinal cord (Summer et al, 1995) and motor neuron diseases (Balice-Gordon et al, Divers et al, 1997;Green and Tolwani, 1999;Green et al, 2001) also involve the cervical spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…AAI causes neck pain, sensory motor deficits, restricted neck movement, and deviation of neck. 1 It can be detected by dynamic CVJ X-ray.…”
Section: Introductionmentioning
confidence: 99%